The Theories of Transnational Terrorism, Relative Deprivation and Fundamentalism in Terrorism Act: The Case Study in Indonesia - Yaza Azzahara Ulyana (International Journal of Business, Economics, and Social Development, 2021)
This research aims to describe the concept of transnational terrorism, relative deprivation and fundamentalism in various terrorism acts that occurred in Indonesia. The research method is qualitative and the type of research is explanatory that explain the cause of terrorism acts that influence by the global actors, fundamentalist that reject the changes and also satisfy the expectation in many aspects in the country from economics to the politics. The results of this research indicate that most of the terrorism cases in Indonesia has various motives starting from their mission in bringing the country led by a caliphate to enforcing the regulations of the country based on the Islamic teachings. Viewed from the perspective of social movements, framing, and resource mobilization strategies seen in the rejection‟s movements of the Transnational Islamic Organization. In addition, the political opportunity structure in the reformation era makes the system and political structure existed became more open. It has provided an opportunity for Transnational Islamic Organization to conduct its movement in criticizing the government.